2016
DOI: 10.1007/s11356-016-8120-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of the exudates released by the brown kelp Lessonia spicata on the toxicity of copper in early developmental stages of ecologically related organisms

Abstract: Lessonia spicata is a key dominant species along the Pacific coast of South America, providing a habitat for many organisms. However, this role can be affected by abiotic stress, such as metals. To counteract the toxic effect, L. spicata, among other seaweeds, releases exudates that bind metals. In this study, tolerances to copper of organisms related to the kelp forest (spores of Ulva lactuca (Chlorophyceae) and L. spicata (Phaeophyceae) and Zoea I of Taliepus dentatus (Milne-Edwards, Crustacea)) were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, they found weak ligands (log K = 8.6) compared with the previous studies mentioned. This was supported by Fellous et al (2017), who demonstrated that exudates of another species of kelp, Lessonia spicata, were able to protect not only the algae itself but also crustacean larva to which the algae provides habitat. Murray et al (2014) tested the impact of exudate ligands in three brown macroalgae under experimental exposure to Cu and Zn and in terms of metal bioavailability.…”
Section: Exudation: Complexing Ligandsmentioning
confidence: 85%
“…Furthermore, they found weak ligands (log K = 8.6) compared with the previous studies mentioned. This was supported by Fellous et al (2017), who demonstrated that exudates of another species of kelp, Lessonia spicata, were able to protect not only the algae itself but also crustacean larva to which the algae provides habitat. Murray et al (2014) tested the impact of exudate ligands in three brown macroalgae under experimental exposure to Cu and Zn and in terms of metal bioavailability.…”
Section: Exudation: Complexing Ligandsmentioning
confidence: 85%